Deviations Due to the Discrete Modeling of the Structures - Hariandja, Binsar H.; Bali, Ika (PRESUNIVE CIVIL ENGINEERING JOURNAL, 2023)
Real existing structures are generally complicated in geometry that might make them unsuitable or difficult forthe analyses. Several assumptions or simplifications are usually made by the practitioners to make them simpler andmay be analyzed in ease. The assumptions and/or simplifications might make the analyses much easier; however,they might create some deviations from the true behavior of the structures, which are in fact, are not known preciselyto the analysts. The paper discusses some examples for simplifications in the analysis or the structural systems. Theexamples include the types of the simplifications, and the deviations that caused by them. The types ofsimplifications are in the case of material behavior, the geometry of the system, an in the case of connectivity of thestructural components. The results signify the importance of wisdom in the setting of the simplifications and theassumptions to make the analyses easier but with dependable results.